Rancang Bangun Media Moblie Learning Mata KuliahTeknologi Multimedia Dan Internet - Lativa Mursyida; Resmi Darni; Ika Parma Dewi (INFORMAL: Informatics Journal, 2021)
Projections of modern technology as one of the implementations of the industrial revolution 4.0. in the world of education, it can be used as a supporter of the concept of learning, thinking, and developing creative and innovative innovations from students, to make the Pencerah become the Golden Indonesia Generation 2045 who is superior and able to compete at the global level. The current situation in the midst of the Covid-19 outbreak, Industrial Revolution Education 4.0 adapts the new curriculum. The curriculum must be able to open a window to the world through digital information, for example: utilizing a smartphone / android in the midst of the Covid-19 outbreak. Educators with a lot of exploring learning techniques and lots of references will be able to implement learning activities effectively even though they are currently in the midst of Covid-19, but all of this is not free from challenges in its implementation, especially educators. Making mobile learning media applications aims to produce learning media that makes it easier for students to learn multimedia and internet courses wherever they are. The development of this application uses the Prototyping development method with Android-based Java programming with Android Studio application software (version 3.3) with Gradle 4.4. This research produces an Android-based mobile learning media application, the features in this interactive module application are RPS, learning materials, videos, and exercises that are in accordance with the Electronic Engineering curriculum learning material, Faculty of Engineering, UNP.